Citral reduces nociceptive and inflammatory response in rodents - Quintans-Júnior, Lucindo José (2011)
Citral (CIT), which contains the chiral enantiomers, neral (cis) and geranial (trans), is the majority monoterpene from Lippia alba and Cymbopogon citratus. The present study aimed to evaluate CIT for antinociceptive and anti-inflammatory activities in rodents. Antinociceptive and anti-inflammatory effects were studied by measuring nociception through acetic acid and formalin tests, while inflammation was verified by inducing peritonitis and paw edema with carrageenan. All tested doses of CIT had significant protection (p<0.001) against acetic acid (0.8%) induced nociceptive behavior and the effects were also similar to morphine while formalin induced nociception was significantly protected (p<0.05) only at higher dose (200 mg/kg) of CIT in the first phase of the test. CIT significantly reduce (p<0.001) nociceptive behavior emanating from inflammation in second phase at all the doses.The pretreatment with CIT (100 and 200 mg/kg) significantly reduced the paw edema induced by carrageenan. Moreover, systemic treatment with CIT (100 and 200 mg/kg) significantly reduced (p<0.001) the leukocyte migration in the carrageenan-induced migration to the peritoneal cavity. Our investigation shows that CIT possess significant central and peripheral antinociceptive effects. It was also verified an anti-inflammatory activity. All together these results suggest that CIT might represent important tool for treatment of painful conditions.